Short- and long-term effects of neonatal pharmacotherapy with epigallocatechin-3-gallate on hippocampal development in the Ts65Dn mouse model of Down syndrome. (1st October 2016) - Stagni, Fiorenza; Giacomini, Andrea; Emili, Marco; Trazzi, Stefania; Guidi, Sandra; Sassi, Martina; Ciani, Elisabetta; Rimondini, Roberto; Bartesaghi, Renata
Highlights: Neonatal treatment with EGCG restores hippocampal neurogenesis in the Ts65Dn model of Down syndrome. Neonatal treatment with EGCG restores hippocampal cellularity in the Ts65Dn model of Down syndrome. Neonatal treatment with EGCG restores hippocampal and cortical synapse development in the Ts65Dn mouse model. The positive effects of neonatal treatment with EGCG are not retained after treatment cessation. Neonatally treated Ts65Dn mice do not exhibit cognitive improvement in adulthood. Abstract: Cognitive disability is an unavoidable feature of Down syndrome (DS), a genetic disorder due to the triplication of human chromosome 21. DS is associated with alterations of neurogenesis, neuron maturation and connectivity that are already present at prenatal life stages. Recent evidence shows that pharmacotherapies can have a large impact on the trisomic brain provided that they are administered perinatally. Epigallocatechin-3-gallate (EGCG), the major polyphenol of green tea, performs many actions in the brain, including inhibition of DYRK1A, a kinase that is over-expressed in the DS brain and contributes to the DS phenotype. Young adults with DS treated with EGCG exhibit some cognitive benefits, although these effects disappear with time. We deemed it extremely important, however, to establish whether treatment with EGCG at the initial stages of brain development leads to plastic changes that outlast treatment cessation. In the current study, we exploited the Ts65Dn mouse model of DS in order to establish whether pharmacotherapy with EGCG during peak of neurogenesis in the hippocampal dentate gyrus (DG) enduringly restores hippocampal development and memory performance. Euploid and Ts65Dn mice were treated with EGCG from postnatal day 3 (P3) to P15. The effects of treatment were examined at its cessation (at P15) or after one month (at P45). We found that at P15 treated trisomic pups exhibited restoration of neurogenesis, total hippocampal granule cell number and levels of pre- and postsynaptic proteins in the DG, hippocampus and neocortex. However, at P45 none of these effects were still present, nor did treated Ts65Dn mice exhibit any improvement in hippocampus-dependent tasks. These findings show that treatment with EGCG carried out in the neonatal period rescues numerous trisomy-linked brain alterations. However, even during this, the most critical time window for hippocampal development, EGCG does not elicit enduring effects on the hippocampal physiology.